Diagnostic cytology of neoplastic lesions in dogs - Hamzah, Hazilawati; M., Abdullah; Rahman, Nor Alimah; Selvarajah, Gayathri Thevi; Arshad, Habibah; Cheng, N. A. B. Y.; Abdul Rahman, Sheikh Omar (Universiti Putra Malaysia Press, 2010)
Cytology is a reliable and minimally invasive method of obtaining tissues for diagnosis. It is a rapid method to be used for differentiating inflammatory from neoplastic disease. Inflammation is easily differentiated from neoplasia based on the presence of inflammatory cells. Ulcerative neoplasm is always secondarily infected by bacteria, and thus inflammatory cells could also be observed. Cytologically, neoplastic cells are classified into three major categories based on certain common cytological features (Meinkoth et al., 2008), namely round, epithelial, and mesenchymal cells (Meinkoth et al., 2008). Cytological images and specific features of neoplastic lesions in dogs from cytology smear, which were obtained from the Veterinary Haematology and Clinical Biochemistry Laboratory, Universiti Putra Malaysia (UPM), were illustrated and briefly described. Round cell tumour was identified as round and discrete neoplastic cells with specific cytoplasmic features, whereas epithelial tumour was identified as clusters of neoplastic cells with closed cytoplasmic attachment, and mesenchymal tumour was identified as spindle neoplastic cells with indistinct cytoplasmic border.